The Makeup of Self-Expression: A Study on The Impact of Self-Congruence on Purchase Intentions With Brand Experience Mediation Among Makeup Artist Consumers - Dana Aditya; Matheous Tamonsang (Jurnal Syntax Transformation, 2023)
A makeup artist (MUA) is a type of business that aims to enhance an individual's appearance through the use of cosmetic materials and tools. The term "makeup" is often associated with altering the facial features, although it can actually be applied to the entire body. The research population consists of consumers who use makeup artist services because of limited data on makeup artist service users, the population data is unknown. According to Fornell (1987), Structural Equation Modeling (SEM) using Partial Least Squares (PLS) based on variances is used to apply theory to exploratory research. In this research, based on the self-congruity theory regarding the use of makeup artist services, especially among female consumers, it is explained that the alignment of the brand's image with the consumer's image does not have a direct impact on the intention to purchase makeup artist services.